2010
DOI: 10.1038/nrrheum.2009.278
|View full text |Cite
|
Sign up to set email alerts
|

Sensors of the innate immune system: their link to rheumatic diseases

Abstract: Evidence strongly suggests that excessive or protracted signaling, or both, by cell-surface or intracellular innate immune receptors is central to the pathogenesis of most autoimmune and autoinflammatory rheumatic diseases. The initiation of aberrant innate and adaptive immune responses in autoimmune diseases can be triggered by microbes and, at times, by endogenous molecules—particularly nucleic acids and related immune complexes—under sterile conditions. By contrast, most autoinflammatory syndromes are gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
61
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 105 publications
(117 reference statements)
0
61
0
4
Order By: Relevance
“…Interestingly, these endosomal TLRs are also able to detect self-nucleic acids (12)(13)(14). Although the endosomal localization isolate TLR3, TLR7, TLR8, and TLR9 away from self-nucleic acids in the extracellular space, still self-RNA or -DNA can become a potent trigger of cell activation when transported into TLR-containing endosomes, and such recognition can result in sterile inflammation and autoimmunity, including SLE (4,15,16). The connection of the endosomal TLRs with SLE originates mainly from mouse models, where TLR7 signaling seems to play a central role.…”
mentioning
confidence: 99%
“…Interestingly, these endosomal TLRs are also able to detect self-nucleic acids (12)(13)(14). Although the endosomal localization isolate TLR3, TLR7, TLR8, and TLR9 away from self-nucleic acids in the extracellular space, still self-RNA or -DNA can become a potent trigger of cell activation when transported into TLR-containing endosomes, and such recognition can result in sterile inflammation and autoimmunity, including SLE (4,15,16). The connection of the endosomal TLRs with SLE originates mainly from mouse models, where TLR7 signaling seems to play a central role.…”
mentioning
confidence: 99%
“…Recently, lots of attention was drawn to studies demonstrating inflammasome activation and IL-1b release in macrophages exposed to MSU or CPPD crystals (6,(15)(16)(17). These findings identified IL-1b as a central mediator and a novel therapeutic target of inflammation in crystal-induced joint diseases (18,19). Anti-IL-1b Ab-based therapies have been successfully used to dampen joint inflammation in gout patients (20).…”
mentioning
confidence: 99%
“…Similarly, other studies showed that mice carrying double deletion of Tlr7 and Tlr9 had stronger disease reduction than those carrying the single Tlr7 deletion. These results suggested that both TLR7 and TLR9 exert disease-promoting effects and that TLR7 engagement is more pathogenic than TLR9 engagement (24). The differential effects of these TLRs may be attributed to increased availability of TLR7-engaging, RNA-containing particles and/or increased downstream signaling by TLR7 compared with TLR9.…”
mentioning
confidence: 95%